Kırklareli University’s Contributions to the Local Economy - Yusuf Cengiz; Naci Tolga Saruç (Maliye Çalışmaları Dergisi)
In addition to providing an educational function, higher education institutions have emerged as economic actors who contribute to the growth of the areas where they are based. Universities produce human capital, boost economic activity, and also assist development. This research examines the direct, indirect, and induced benefits that Kırklareli University, founded in 2007, provides to the local economy. The purpose of this research is to calculate the overall expenditures incurred by Kırklareli University, the expenditures incurred by higher education students, and the economic worth of the employed workforce in general. In this regard, a questionnaire was administered to 393 Kırklareli University students to establish their expenses. According to the collected data, students’ average monthly spending is 3,144 TL. From this perspective, the economic effect of student spending on the city is around 650 million TL. In addition, the indirect employment impact of staff expenses from the university budget and student spending involves a total of 5,563 individuals. The entire direct and indirect revenue impact is 820 million TL. In addition to the direct and indirect benefits, the research has projected the university to generate 2,673,830,832 TL in induced revenue effects and to have an induced employment impact of 20,623 individuals. The total induced impact regarding income accounts for around 10% of the province’s gross domestic product. According to the findings, Kırklareli University has been a significant participant in the city’s economy due to how it spends from its own budget, its student expenditures, and the employment statistics it has generated.